Fibrinogen activates the capture of human plasminogen by staphylococcal fibronectin-binding proteins - FOSTER, TIMOTHY (My University, 2017)
Invasive bacterial pathogens can capture host plasminogen (Plg) and al- low it to form plasmin. This process is of medical importance as surface-bound plas- min promotes bacterial spread by cleaving tissue components and favors immune evasion by degrading opsonins. In Staphylococcus aureus , Plg binding is in part mediated by cell surface fibronectin-binding proteins (FnBPs), but the underlying molecular mechanism is not known. Here, we use single-cell and single-molecule techniques to demonstrate that FnBPs capture Plg by a sophisticated activation mechanism involving fibrinogen (Fg), another ligand found in the blood. We show that while FnBPs bind to Plg through weak ( 200-pN) molecular bonds, direct inter- action of the adhesins with Fg through the high-affinity dock, lock, and latch mech- anism dramatically increases the strength of the FnBP-Plg bond (up to 2,000 pN). Our results point to a new model in which the binding of Fg triggers major confor- mational changes in the FnBP protein, resulting in the buried Plg-binding domains being projected and exposed away from the cell surface, thereby promoting strong interactions with Plg. This study demonstrated a previously unidentified role for a ligand-binding interaction by a staphylococcal cell surface protein, i.e., changing the protein orientation to activate a cryptic biological function